AB0462 IMMUNIZATIONTO RITUXIMAB IS MORE FREQUENT IN AUTOIMMUNE SYSTEMIC AUTOIMMUNE DISEASES THAN IN RHEUMATOID ARTHRITIS AND MAY BE MANAGED BY SWITCHING FROM RITUXIMAB TO OFATUMUMAB. (June 2019) - Combier, Alice; Nocturne, Gaetane; Henry, Julien; Belkhir, Rakiba; Pavy, Stephane; Mariette, Xavier; Seror, Raphaèle
Abstract : Background: The most widely used B cell targeted therapies in auto-immune diseases (AID) is Rituximab (RTX), a murine chimeric monoclonal antibody. Among RTX's side effects, immunization and anti-drug antibodies to RTX (RTX-ADA) production have been reported but their consequences are poorly described. The immunization rate against RTX in rheumatoid arthritis (RA) is 2, 7-9, 2% and it seems to be higher in other sAID although data is lacking. Objectives: We aimed to evaluate the frequency, consequences and predictive factors of RTX-ADA in RA and sAID, as well as the use of an alternative B-cell targeted therapy, ofatumumab (OFA) in case of RTX-ADA. Methods: All patients with RA or sAID treated with RTX from 2012 to 2017 in our tertiary reference centre for sAID were retrospectively studied. Patients who were tested for RTX-ADA were identified. Clinical and biological characteristics of RTX immunized patients were compared to those of non-immunized patients. For patients treated with OFA, clinical and biological efficacy was obtained before and after treatment. Results: 199 patients were treated with RTX (RA: 124, sAID: 75 including 38 primary Sjögren's Syndrome (pSS), 15 systemic lupus erythematous, 7 myositis, 6 overlap syndrome, 5 ANCA-associated vasculitides and 4 other sAID). Among the 62/199 (31.1%) tested for RTX-ADA, 14 were positive: 3/35 RA (8, 6%) and 11/27 (40, 7%) other sAID, (p=0.005). Among the whole RTX-treated patients, the frequency of RTX-ADA was 2, 4% and 14, 7% (p=0.003) in RA and in other sAID, respectively. Most of the immunized patients experienced delayed infusion reactions (11/14 [78, 5%]). Delayed reactions were observed within the first 15 days after the infusion, and after a median 2 cycles [range; 1-2]. They were mainly rash (72, 7%), fever (54.5) and/or abdominal pain (36, 3%). Predictive factors of immunization were a sAID compared to RA (40, 7% vs 8, 6%, p=0.005), and young age (50.5 vs 61.5 years, p=0.003). Neither hypergammaglobulinemia, rheumatoid factor, disease activity, nor associated immunosuppressive therapy were associated with RTX-ADA. Among 23 tested patients with SLE or pSS, anti-SSA antibodies tended to be more frequent in immunized patients than non immunized (9/10 (90.0%) vs. 8/13 (61.5%), p=0.18). Three pSS patients immunized against RTX were treated with OFA because of associated cryoglobulinemic vasculitis or MALT lymphoma. All 3 experienced complete remission of their disease. Relapse occurred in 2 patients, one with MALT lymphoma after 14 months, one with cryoglobulinemic vasculitis after 10 months and were retreated successfully with OFA. No adverse events were reported. Conclusion: Our results show that immunization against RTX is more frequent in other sAID than in RA. Testing for ADA must be performed in patients with infusion reactions. Patients immunized to RTX might be treated efficiently with OFA, which should be further evaluated in sAID. Disclosure of Interests: Alice Combier: None declared, Gaetane Nocturne: None declared, Julien Henry: None declared, Rakiba Belkhir: None declared, Stephane Pavy: None declared, Xavier Mariette Grant/research support from: Servier, Consultant for: AstraZeneca, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Pfizer, UCB Pharma, Raphaèle Seror: None declared